Proof-of-concept clinical trial of etokimab shows a key role for IL-33 in atopic dermatitis pathogenesis - Chen, Yi-Ling; Gutowska-Owsiak, Danuta; Hardman, Clare S; Westmoreland, Melanie; MacKenzie, Teena; Cifuentes, Liliana; Waithe, Dominic; Lloyd-Lavery, Antonia; Marquette, Allison; Londei, Marco; Ogg, Graham (Science translational medicine, 2019)
Targeted inhibition of cytokine pathways provides opportunities to understand fundamental biology in vivo in humans. The IL-33 pathway has been implicated in the pathogenesis of atopy through genetic and functional associations. We investigated the role of IL-33 inhibition in a first-in-class phase 2a study of etokimab (ANB020), an IgG1 anti-IL-33 monoclonal antibody, in patients with atopic dermatitis (AD). Twelve adult patients with moderate to severe AD received a single systemic administration of etokimab. Rapid and sustained clinical benefit was observed, with 83% achieving Eczema Area and Severity Index 50 (EASI50), and 33% EASI75, with reduction in peripheral eosinophils at day 29 after administration. We noted significant reduction in skin neutrophil infiltration after etokimab compared with placebo upon skin challenge with house dust mite, reactivity to which has been implicated in the pathogenesis of AD. We showed that etokimab also inhibited neutrophil migration to skin interstitial fluid in vitro. Besides direct effects on neutrophil migration, etokimab revealed additional unexpected CXCR1-dependent effects on IL-8-induced neutrophil migration. These human in vivo findings confirm an IL-33 upstream role in modulating skin inflammatory cascades and define the therapeutic potential for IL-33 inhibition in human diseases, including AD.